Rancang Bangun Sistem Deteksi Lingkungan Kerja Industri Berbasis GSM - Bahtiar Adip Rifa'i; Waluyo Waluyo; Rachmad Saptono (Jurnal Jaringan Telekomunikasi, 2021)
Industrial accidents are accidents that occur in the workplace, especially in an industrial environment. The most important factors in the occurrence of work accidents are technical equipment, work environment, and the workers themselves. Lighting that is not enough to illuminate workers when using machines can cause work accidents during the production process. In addition, hot conditions can also cause work accidents because hot temperatures make the body uncomfortable at work, reduce agility, interfere with the carefulness of the brain, and ease emotions so that workers cannot concentrate and can cause work accidents. The purpose of this research is to create a system that can detect temperature, smoke, and light in a GSM-based industrial environment. This system can help prevent industrial accidents by obtaining information about industrial environmental conditions for workers in the form of SMS. Temperature, smoke, and light sensors will send SMS information when each sensor exceeds the threshold value specified in the program. Information delivery is carried out using 3 different providers, namely Three, Indosat, and Telkomsel by comparing the amount of delay. The test results can be concluded that the three sensors can work well. The temperature sensor can detect temperature with an average error value of 0.03%. The smoke sensor can detect smoke with an average value of 0%. Provider Three can send information with a small average delay, namely 1.46s. Indosat providers can send information with an average delay of 3.68s. Telkomsel providers can send information with an average delay of 1.52s.